Optimization of Digital Finance to Improve the Performance of Klubanotic MSMEs in Brebes Regency - Utami, Yuni; Amalia, Mei Rani; Murdiati, Sri (ASEAN Journal of Empowering Community, 2023)
The rapid development of technology in Indonesia has changed the way of life in many aspects, including the financial sector. Financial technology (fintech) is one of the technological developments that has the potential to increase the productivity and efficiency of micro, small, and medium enterprises. (UMKM). SMEs play an important role in the Indonesian economy, contributing 60.5% to GDP and 96.9% to the national workforce. However, MSMEs face challenges in adopting digital financial technology due to a lack of digital skills and knowledge in accounting practices. To address this challenge, training programs on financial management systems, including accounting software applications, can be developed to help SMEs manage their finances effectively. Klubanostic UMKM Brebes, a community of MSMEs producing various types of products, faces similar challenges. By practicing with accounting software applications, SMEs can improve their accounting practices, which will contribute to the growth of their business. Fintech is a dynamic concept that brings about a paradigm shift in the financial and business sectors, with the potential to offer efficiency, cost reduction, process improvement, speed, flexibility, and innovation for SMEs.